1998
DOI: 10.2223/jped.448
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus (HCV) in children and adolescent hemophiliacs

Abstract: IntroduçãoO efeito indesejável mais notório das transfusões sangüíneas é a aquisição de hepatites virais. As múltiplas exposições dos hemofílicos ao uso de derivados do sangue colocam este grupo em extremo risco na aquisição destas hepatites. Comprovadamente implicados nas hepatites pós-transfusionais, desenvolvidas pelos hemofílicos, ResumoObjetivo: Avaliar a soroprevalência de infecção pelo HCV entre hemofílicos no Estado do Pará e a possível relação com nível sérico de enzimas hepáticas, tipo de hemofilia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Despite of inability to determine the infectious status of many cases of haemophilia A and B through their recording profiles, we could estimate that our HCV positive cases were fewer than those reported from the Gilan. Our data are similar to [8] and Turkey (Kocabas et al) [9]. This study showed lower occurrence of HBs-Ag positive cases compared with the similar reports from neighbouring countries.…”
supporting
confidence: 91%
“…Despite of inability to determine the infectious status of many cases of haemophilia A and B through their recording profiles, we could estimate that our HCV positive cases were fewer than those reported from the Gilan. Our data are similar to [8] and Turkey (Kocabas et al) [9]. This study showed lower occurrence of HBs-Ag positive cases compared with the similar reports from neighbouring countries.…”
supporting
confidence: 91%
“…In the Amazon region, the estimated prevalence of HCV infection ranges from 1% to 3%, with higher rates being recorded in vulnerable groups, such as PWUDs (23.1%), patients undergoing hemodialysis (8.4%), and patients with hemophilia (48.4%) [5,[20][21][22][23][24]29,36,46]. The prevalence of HCV infection detected in this study was 10.7%, and most of these infections were classified as active (7.8%).…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, resistance-associated substitutions (RASs) located in NS3, such as V36L, V55A, Q80L, and R155K for subtype 1a, and T54S, V55A, R117H, and D168G for subtype 1b, have already been identified in HCV-infected Brazilians [19]. In the Amazon region (northern Brazil), several epidemiological studies indicate a high prevalence of HCV infections and the predominance of genotype 1 in different population groups, such as indigenous people, people living in riverside communities, blood donors, patients undergoing hemodialysis, patients with multiple blood transfusions, and PWUDs [5,18,[20][21][22][23][24][25]. Factors associated with parenteral and sexual exposure to HCV have been detected, including: Shared use of manicure and pedicure instruments, use of home-sterilized needles and syringes, unprotected sexual intercourse, more than 12 sexual partners, daily drug use, drug use for more than three years, and shared use of drug paraphernalia [5,[26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, there is a high prevalence of hepatotrophic viruses in the Amazon region with virological peculiarities, such as genotype F of HBV [8,9] and hepatitis D virus [10]. Many Brazilian studies, as well as international studies, describe the prevalence of hepatotrophic viruses among specific groups, such as blood donors [11], patients in hemodialysis programs [12][13][14], hemophiliacs [15], afro-descendants [16], mental disease patients [17] and hepatitis patients [18,19]. Due to a lack of studies conducted on the Brazilian northeastern semiarid region, we examined the distribution of hepatitis A (HAV), B (HBV) and C (HCV) serological markers in this population.…”
mentioning
confidence: 99%